(untitled) (Journal of Contemporary Philology, 2025)
This paper discusses, from a qualitative and quantitative corpus-based perspective, the features and challenges in comparable terminology in the field of migration in Arabic, Italian, and English. More specifically, it examines terminology related to the migration process, migration agents and socially related issues such as marriage and adoption, taking into account linguistic, social, and cultural obstacles in identifying suitable translation candidates when applying European law to languages that do not share similar juridical frameworks and social practices. The aim of the paper is to identify common linguistic issues and their root causes and to present best practices for adequately covering of this terminological area.